(untitled) (Global Journal of Science Frontier Research, 2020)
One of the methods for solving problems in mechanics is the use of Lagrangian formalism.By function of Lagrange or Lagrangian in the mechanics is understood the difference between the kinetic and potential energy of the system ofin question.If we integrate the Lagrangian with respect to time, we obtain the first main Hamilton function, called the action.In the general case kinetic energy of system depends on speed, and potential energy depends on coordinates. In the case of the conservatism of system during its motion she selects the way, with which the action is minimum. However, the record of Lagrangian, accepted in the electrodynamics does not entirely satisfy the condition of the conservatism of system. The vector potential, in which moves the charge, create the strange moving charges, and the moving charge interacts not with the field of vector potential, but with the moving charges, influencing their motion. But this circumstance does not consider the existing model, since. vector potential comes out as the independent substance, with which interacts the moving charge. Moreover, into the generalized momentum of the moving charge is introduced the scalar product of its speed and vector potential, in which the charge moves.